Exercise-augmented THSD7B exhibited a positive prognostic implication and tumor-suppressed functionality in pan-cancer - Luo, Zhiwen; Zhu, Jinguo; Fang, Zhengyuan; Xu, Rui; Wan, Renwen; He, Yanwei; Chen, Yisheng; Chen, Shuo; Wang, Qing; Liu, Qizhi; Chen, Shiyi (Frontiers in Immunology, 2024)
Background: Breast cancer, one of the most prevalent malignancies among women worldwide, has rising incidence rates. Physical activity, particularly exercise, has emerged as a significant modifier of cancer prognosis, influencing both tumor biology and patient outcomes.In this study, we utilized a murine breast cancer model, dividing mice into a control group and an exercise group; the latter underwent 21 days of voluntary running. We conducted RNA sequencing, bioinformatics analysis, pan-cancer analysis, and cellular experiments to investigate the underlying mechanisms influenced by exercise.Exercise led to a significant reduction in tumor size and weight. Post-exercise mRNA sequencing indicated a notable upregulation of THSD7B in the exercised mice, with significant alterations observed in pathways such as MicroRNAs in cancers and the Calcium signaling pathway. In a broader cancer context, THSD7B showed considerable expression variability, being significantly downregulated in several cancers, correlating with positive prognostic outcomes in PRAD, LAML, KIRC, and GBM and highlighting its potential role as a prognostic marker and therapeutic target. THSD7B expression was also negatively associated with processes of breast cancer cell proliferation, migration, and invasion.This study underscores the dual role of exercise in modulating gene expression relevant to tumor growth and highlights the potential of THSD7B as a therapeutic target in cancer. Future research should further explore the specific mechanisms by which exercise and THSD7B influence cancer progression and develop immunotherapy-enhanced strategies to change patient outcomes in clinical settings.